2009
DOI: 10.1159/000236445
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Brain White Matter Diffusion Anisotropy and Mean Diffusivity with Reaction Time in an Oddball Task

Abstract: Background: Reaction time (RT) is a frequently used measure of information processing speed, but the underlying physiological and anatomical conditions are not yet fully understood. A correlation between measures of white matter (WM) ultrastructural properties and RT is expected – particularly for those WM tracts that are involved in the attentional system of the brain. Methods: Diffusion tensor imaging data were acquired in 43 unrelated healthy subjects (age: 22.7 ± 1.8 years), and RT was measured during an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 96 publications
4
23
0
Order By: Relevance
“…Thus, taken together, there seems to be a physiological association between blood flow, BOLD signal fluctuations, and EEG features in the alpha band (IAF and power) in networks relevant for specific tasks involving attention and working memory. Further support of the view of an association to task performance is provided by studies that demonstrated a relation of FA (within association fascicles) with reaction time (Konrad et al, 2009), cognitive performance (Madden et al, 2009;Moseley et al, 2002;Sasson et al, 2010), and mental disorders (Begre et al, 2008). Our results of the present study, together with previous work, indicate that transient activity of FCNs is related to baseline activity of the same FCNs, and structural connectivity within those FCNs.…”
supporting
confidence: 85%
“…Thus, taken together, there seems to be a physiological association between blood flow, BOLD signal fluctuations, and EEG features in the alpha band (IAF and power) in networks relevant for specific tasks involving attention and working memory. Further support of the view of an association to task performance is provided by studies that demonstrated a relation of FA (within association fascicles) with reaction time (Konrad et al, 2009), cognitive performance (Madden et al, 2009;Moseley et al, 2002;Sasson et al, 2010), and mental disorders (Begre et al, 2008). Our results of the present study, together with previous work, indicate that transient activity of FCNs is related to baseline activity of the same FCNs, and structural connectivity within those FCNs.…”
supporting
confidence: 85%
“…However, in the TBSS effect-size map (Fig. 5), some clusters exhibiting an apparent relationship with choice RT are present in regions similar to those found in adults (Konrad et al, 2009;Tuch et al, 2005), suggesting that regions supporting visuospatial attention may also be related to children's performance on the present task. Future studies are necessary to address this in more detail.…”
Section: Discussionmentioning
confidence: 73%
“…Alternatively, the variability in motor system MD may reflect individual differences in the architecture of the motor system (perhaps differences in the underlying connectivity) that emerge earlier during brain development and remain stable in spite of superimposed biological changes associated with maturation. This is plausible since individual differences in behavioural performance have been associated with MD variability in adults (Konrad et al, 2009;Piras et al, 2010) as well as children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations